2018
DOI: 10.1093/nar/gky094
|View full text |Cite
|
Sign up to set email alerts
|

Structural rearrangements in the mitochondrial genome of Drosophila melanogaster induced by elevated levels of the replicative DNA helicase

Abstract: Pathological conditions impairing functions of mitochondria often lead to compensatory upregulation of the mitochondrial DNA (mtDNA) replisome machinery, and the replicative DNA helicase appears to be a key factor in regulating mtDNA copy number. Moreover, mtDNA helicase mutations have been associated with structural rearrangements of the mitochondrial genome. To evaluate the effects of elevated levels of the mtDNA helicase on the integrity and replication of the mitochondrial genome, we overexpressed the heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 58 publications
7
16
0
Order By: Relevance
“…Another possibility considered by Sfeir and coworkers was an uncontrolled activity of DNA metabolic enzymes. In agreement with this idea, in our recent study on mtDNA replication in Drosophila melanogaster, we observed that an elevated expression of wild-type Twinkle resulted in the accumulation of DmtDNA, which expanded clonally to the extent that no wild-type mtDNA was detected by Southern-blotting (Ciesielski et al, 2018). Deletions have also been reported for mice overexpressing the wild-type helicase (Ylikallio et al, 2010).…”
Section: The Role Of the Replisome In The Formation Of Mtdna Deletionssupporting
confidence: 81%
See 4 more Smart Citations
“…Another possibility considered by Sfeir and coworkers was an uncontrolled activity of DNA metabolic enzymes. In agreement with this idea, in our recent study on mtDNA replication in Drosophila melanogaster, we observed that an elevated expression of wild-type Twinkle resulted in the accumulation of DmtDNA, which expanded clonally to the extent that no wild-type mtDNA was detected by Southern-blotting (Ciesielski et al, 2018). Deletions have also been reported for mice overexpressing the wild-type helicase (Ylikallio et al, 2010).…”
Section: The Role Of the Replisome In The Formation Of Mtdna Deletionssupporting
confidence: 81%
“…Earlier reports did in fact indicate low levels of DSB repair in mitochondria (Bacman et al, 2009;Fukui and Moraes, 2009). Overall, the correlation between the frequency of DSBs and deletion formation in mitochondria appears to be well documented (Fukui and Moraes, 2009;Ciesielski et al, 2018;Nissanka et al, 2018), and in the light of these reports, including our own studies, they are very likely related. Perhaps, the coexistence of the rapid degradation of linearized mtDNA and the low efficiency of DSB repair could actually explain the clonal expansion phenomenon, as the rapid degradation of many cleaved molecules (which could arise in abundance, for example, from uncoupling of the mitochondrial replisome, as discussed in the next section) would give advantage to the replication of those few repaired DmtDNA, which consequently would repopulate mitochondria.…”
Section: Formation Of Mtdna Deletionssupporting
confidence: 77%
See 3 more Smart Citations